Artifisial High Altitude Training dalam peningkatan kapasitas vital paru atlet - Arimbi Arimbi (Seminar Nasional LP2M UNM, 2019)
This study know how the effects of routine training with artificial high altitude training methods by using elevation mask to improve the vital capacity of lung athletes. Sports will cause endurance and strength of respiratory muscles to increase so that the ability to expand the lungs increases, thus it is expected that more oxygen is bound for further use in energy production, besides that, exercise will result in increased ability of respiratory muscles to overcome the resistance of respiratory air flow. This results in an increase in air volume. This study is a pre-experimental study or pre-experimental design which is a study that is used to find a causal relationship where randomization is not done and does not use a control group. The research design uses The one-group Pre-posttest Design. In this study a group of subjects or experimental units were selected. The instrument used in this study is to use peak flow meters for vital lung capacity. Data that will be analyzed are the results of the initial test and the final test of measurement.